2018
DOI: 10.1177/0014402918793399
|View full text |Cite
|
Sign up to set email alerts
|

Functional Communication Training: The Strength of Evidence Across Disabilities

Abstract: Functional communication training (FCT) is a commonly used, often recommended intervention that involves teaching a functionally equivalent communicative response to replace challenging behavior. The purpose of this literature review was to evaluate the strength of the evidence for the use of FCT. A systematic review of the literature resulted in the identification of 215 single-case-design articles that evaluated the efficacy of FCT to reduce challenging behavior for individuals diagnosed with a disability. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 39 publications
(68 reference statements)
0
36
0
2
Order By: Relevance
“…As discussed in more detail below in the section on "next steps," organizations can develop professional and consumer standards internally, or adopt external standards when they are available. Broad examples of professional standards include the extent to which the service uses evidence-based practices (i.e., specific interventions such as functional communication training; e.g., Gerow et al, 2018), best practices (i.e., specific assessments such as functional analysis of challenging behavior; Iwata et al, 1982Iwata et al, /1994, services conform to an evidence-based practice of ABA framework (Slocum et al, 2014), all seven dimensions of ABA are represented, practitioners consistently practice within their scope of practice and competence, practitioners adhere to the BACB's Professional and Ethical Compliance Code for Behavior Analysts ©, and other aspects of service delivery and daily operations captured by standards developed by external entities such as the BHCOE or CASP. Examples of concrete outcome standards may be harder to come by so organizations may need to rely more heavily on an internal approach to standards development.…”
Section: Asdq Definedmentioning
confidence: 99%
“…As discussed in more detail below in the section on "next steps," organizations can develop professional and consumer standards internally, or adopt external standards when they are available. Broad examples of professional standards include the extent to which the service uses evidence-based practices (i.e., specific interventions such as functional communication training; e.g., Gerow et al, 2018), best practices (i.e., specific assessments such as functional analysis of challenging behavior; Iwata et al, 1982Iwata et al, /1994, services conform to an evidence-based practice of ABA framework (Slocum et al, 2014), all seven dimensions of ABA are represented, practitioners consistently practice within their scope of practice and competence, practitioners adhere to the BACB's Professional and Ethical Compliance Code for Behavior Analysts ©, and other aspects of service delivery and daily operations captured by standards developed by external entities such as the BHCOE or CASP. Examples of concrete outcome standards may be harder to come by so organizations may need to rely more heavily on an internal approach to standards development.…”
Section: Asdq Definedmentioning
confidence: 99%
“…Z výzkumné studie, jejímž cílem bylo definovat společné charakteristiky nejčastějších účastníků FCT, můžeme konstatovat, že ve více než polovině případů je FCT indikován u jedinců s PAS a dále u jedinců s mentálním a kombinovaným postižením. V 70 % se jedná o jedince mužského pohlaví (Gerow et al, 2018). Často řešeným problémem, objevujícím se napříč mnoha výzkumy, je návrat nežádoucího chování po ukončení nebo v průběhu FCT.…”
Section: Interpretace Poznatků Z Výzkumu Zabývajícího Se Využítím Fctunclassified
“…Suess et al (2020) uvádí, že pokud je sociálně přijatelná odpověď naučena mimo kontext, tedy v době, kdy se žádné nežádoucí chování nevyskytuje, je pravděpodobné, že se jedinec naučí tuto alternativní odpověď využívat namísto nežádoucího chování. V rámci některých námi analyzovaných studií byla úspěšně využívána strategie pracující se signalizací dostupnosti posílení, což v kombinaci s vyhasínáním nežádoucího chování vedlo k jeho snížení (Boyle et al, 2018;Davis et al, 2018;Greer et al, 2019). Výzkumy se rovněž shodují na efektivitě implementace procesu vyhasínání nežádoucího chování v rámci FCT.…”
Section: Interpretace Poznatků Z Výzkumu Zabývajícího Se Využítím Fctunclassified
“…Furthermore, it has accumulated sufficient research support to be deemed an evidence-based practice for individuals with ASD, intellectual disability, other health impairments, and multiple disabilities (Gerow, Davis, Radhakrishnan, Gregori, & Rivera, 2018;Muharib & Wood, 2018;Wong et al, 2015). Although much of the research has targeted individuals aged 5 to 11 years, researchers have demonstrated FCT's effectiveness across both younger and older individuals (Gerow et al, 2018). Table 2 lists the three steps of FCT and serves as an implementation checklist to support procedural integrity.…”
Section: Defining Functional Communication Trainingmentioning
confidence: 99%
“…FCT is a strategy that addresses challenging behavior by teaching individuals to use socially acceptable communicative responses to access reinforcers (Carr & Durand, 1985). Furthermore, it has accumulated sufficient research support to be deemed an evidence-based practice for individuals with ASD, intellectual disability, other health impairments, and multiple disabilities (Gerow, Davis, Radhakrishnan, Gregori, & Rivera, 2018; Muharib & Wood, 2018; Wong et al, 2015). Although much of the research has targeted individuals aged 5 to 11 years, researchers have demonstrated FCT’s effectiveness across both younger and older individuals (Gerow et al, 2018).…”
Section: Defining Functional Communication Trainingmentioning
confidence: 99%